Best practices for dust control in metal/nonmetal mining - Colinet, Jay (Information circular (National Institute for Occupational Safety and Health) ;, 2010)
This handbook identifies engineering controls that can assist underground and surface metal/nonmetal mining operations in reducing worker exposure to respirable silica dust.